Intraspecific variation in erythrocyte sizes among populations of Hypsiboas cordobae (Anura, Hylidae). - Baraquet, Mariana (2013)
We studied the morphology and size of erythrocytes of H. cordobae, and analysed the geographic variation of this character along the distribution of the species, in relation to the latitudinal and altitudinal distances. Erythrocyte shape of the H. cordobae is ellipsoidal and the nuclei are also ellipsoidal and centrally oriented. Erythrocyte and nuclear size showed significant differences among populations, with the highest mean size corresponding to the population of Achiras (low altitude site) and the lowest mean size to Los Linderos (high altitude site). There was no significant relationship between the latitude of each population and the both erythrocyte and nuclear size. The altitudinal variation in erythrocyte cell size may be attributable to the surface available for gas exchange; a small erythrocyte offers a possibility of greater rate of exchange than a larger one. Our results are consistent with studies of other amphibians, where intraspecific comparisons of populations at different altitudes show that individuals at higher altitudes are characterized by smaller erythrocytes.